Development of isotope-enriched phosphatidylinositol-4- and 5-phosphate cellular mass spectrometry probes. Issue 7 (8th January 2021) - Joffrin, Amélie M.; Saunders, Alex M.; Barneda, David; Flemington, Vikki; Thompson, Amber L.; Sanganee, Hitesh J.; Conway, Stuart J.
Abstract : We report the synthesis of deuterium-labelled derivatives of phosphatidylinositol 4-phosphate and phosphatidylinositol 5-phosphate, and demonstrate their use in quantifying levels of endogenous phospholipids in cells. Abstract : Synthetic phosphatidylinositol phosphate (PtdIns P n ) derivatives play a pivotal role in broadening our understanding of PtdIns P n metabolism. However, the development of such tools is reliant on efficient enantioselective and regioselective synthetic strategies. Here we report the development of a divergent synthetic route applicable to the synthesis of deuterated PtdIns4 P and PtdIns5 P derivatives. The synthetic strategy developed involves a key enzymatic desymmetrisation step using Lipozyme TL-IM®. In addition, we optimised the large-scale synthesis of deuterated myo -inositol, allowing for the preparation of a series of saturated and unsaturated deuterated PtdIns4 P and PtdIns5 P derivatives. Experiments in MCF7 cells demonstrated that these deuterated probes enable quantification of the corresponding endogenous phospholipids in a cellular setting. Overall, these deuterated probes will be powerful tools to help improve our understanding of the role played by PtdIns P n in physiology and disease.